Pencegahan resiko jatuh dan anger manajemen berbasis keluarga pada lansia pesisir dengan edukasi dan monitoring Rumah Tangga - Diyan Mutyah; Hidayatus S; Dya Sustrami; Lela Nurlela; Sukma Ayu (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2026)
Older adults are a vulnerable population at risk of experiencing both physical and psychological health problems. Falls are one of the leading causes of injury among older adults, while poor anger management can negatively affect psychosocial well-being and family relationships. Coastal communities often face environmental challenges, such as slippery floors, inadequate lighting, and crowded home layouts, which may increase the risk of falls among older adults. This community service program aimed to improve family knowledge and skills in fall risk prevention and anger management among older adults living in coastal areas through educational interventions and household-based monitoring. The program involved 35 older adults and 35 family caregivers in the coastal area of Gesik Cemandi Village, Sedati District, Sidoarjo Regency. The intervention consisted of health education sessions, demonstrations of home environment modifications, anger management training, and four weeks of household monitoring. Program evaluation was conducted using pretest–posttest assessments and a home safety observation checklist. The results showed an increase in the average knowledge score from 61.3 before the intervention to 85.7 after the intervention. A total of 82.9% of families were able to identify fall risk factors, while 77.1% successfully applied anger management strategies in caring for older adults. Household monitoring also revealed improvements in home safety conditions, particularly in lighting, furniture arrangement, and bathroom safety. Family-based education and household monitoring effectively enhanced family capacity to support the physical and psychological well-being of older adults in coastal communities.